Children’s fracture: an experience from a zonal hospital in Nepal - Paudel, KP; Thapa, SK (Journal of College of Medical Sciences-Nepal, 2010)
A retrospective study of all paediatric fractures presenting to Bharatpur hospital in two years was undertaken. The aim of this study is to find out incidence of fractures in children attending Bharatpur Hospital, their risk factors, problem magnitude and problem areas, preventability, disease burden socio-economically, so that it will be helpful in formulations of plans and policies at national or regional level to prevent or to decrease the injury incidences among children in populations in Nepal. Details are collected from children with fractures attending Bharatpur hospital in emergency, outdoor and indoors including their variables, geographical distribution, injury mechanism and pattern, time of seeking treatment and places etc. the study period is from January 2008 to December 2009. 1216 children were treated ranging in age from 0 to 14 year. 35% of cases were from Chitwan district. Incidence of fracture increases with age. Left sided limbs had more fractures as they assume the role of protection. 67% of children's fractures occurred in males. The majority of fractures in children involve the upper limb i.e. 80%. Supracondylar fractures of humerus predominate all incidences. Mode of injury in majority of the cases was fall. Key words: Children; fractures; humerus DOI: 10.3126/jcmsn.v6i2.3611 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 14-17